The 3D paleontology and the laser scanner - Medeiros, Marco André Malmann; Favera, Jorge Carlos Della; Reis, Márcia Aparecida Fernandes dos; Silva, Tito Lyvio Vieira e; Oliveira, Eduardo Barreto; Biassusi, Rafael Aguiar; Silveira, Renan Garcia da (Anuário do Instituto de Geociências, 2007)
The introduction of laser scanning for imaging let paleontologists determinate, with higher detail level, the taphonomic positions of fossils in a rock outcrop. It also registers, with millimeters precision, the shape and position of some ichnofossil, like tracks and footprints. With all that, entire digital rock outcrops can be created and preserved for future studies. The initial data acquired by the software Cyclone is editable in any CAD software, allowing their rendering as well as the possibility of a future reconstruction using prototypes.